242 #Goasco20: success of a new twitter hashtag to promote gynaecological oncology specific information during asco 2020 virtual annual meeting. (4th December 2020) - Bhandoria, Geetu; Bilir, Esra; Uwins, Christina; Mackenzie, Graham; Selcuk, Ilker
Abstract : Introduction/Background: Scientific conferences promote specific hashtags for delegates to use. With the COVID-19 pandemic resulting in the cancellation of physical meetings there is considerable interest in understanding Twitter use at virtual events. Here we assess the reach of '#goASOCO20', a new hashtag created to disseminate Gynaecological Oncology specific information from the American Society of Clinical Oncology (ASCO) 2020 Virtual Annual Meeting 29th May to 1st June 2020. Methodology: Prospective observational study of tweets/retweets associated with #goASCO20. All tweets using #goASCO20/#ASCO20 during ASCO 2020 were extracted using NodeXL. Data was analysed in Excel identifying individual tweets, tweeters, retweets and retweeters. Analysing original tweets (replies excluded) #goASCO20 was compared to #ASCO20 (official hashtag), #gyncsm and #SGOatASCO. Results: 1, 811 tweeters used #goASCO20/#ASCO20 in 11, 530 tweets. These tweets received 27, 962 retweets. 12.4% (224) of tweeters received 80% of all retweets, while 34.2% (619) received no retweets. 7, 644 accounts tweeted/retweeted using #ASCO20 hashtag, producing 11, 455 tweets and 27, 888 retweets. 11.1% of accounts (850) only tweeted, 76.3% (5, 833) just retweeted, and 12.6% (961) both tweeted and retweeted. #goASCO20 was used in 200 tweets and generated 262 retweets. This activity stemmed from 38 accounts that tweeted/retweeted using #goASCO20. Of these accounts 13% (5) just tweeted, 74% (28) just retweeted and 13% (5) both tweeted and retweeted. Top hashtags used during ASCO 2020 are shown in table 1 . Figure 1 compares Gynaecology related hashtags used during the conference. #goASCO20 hashtag was number 13 by tweets and 27th by retweets during the conference period. Conclusion: '#goASCO20', a unique Gynaecological Oncology hashtag was created to disseminate Gynaecological Oncology information from ASCO 2020 virtual event. #goASCO20 was one of several gynaecological oncology hashtags used. Each of these were used by relatively small groups of individuals. Discussions were fragmented resulting in an overall lower profile for Gynaecological Oncology related tweets compared to general tweeting during ASCO 2020. The use of Twitter in academia is increasing. Its use during such conferences facilitates the spread of clinical knowledge; arguably more than any other academic platform. Gynaecological oncology tweeting needs coordination and agreement on a common hashtag to organise content at virtual events and between meetings. Disclosures: Esra Bilir: Member of Communication and Social Media Committee at The European Network of Young Gynae Oncologists (ENYGO) since May 2020. Christina Uwins: Nothing to declare Graham Mackenzie: Nothing to declare. İlker Selçuk: European Network of Young Gynae-Oncologists (ENYGO) Executive Group Member (2017–2021) (ENYGO Social Media Committee Chair) Geetu Bhandoria: Nothing to declare